Evidence-based intervention programmes addressing affective forecasting errors in elite sport retirement - Lavallee, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Several career transitions programmes for athletes have been developed in countries around the world recently, based on the belief that intervention at the organisational level can be a useful means for facilitating the career transition process. These programmes vary in their focus from educating athletes on lifestyle management to helping others cope with various forms of sport transitions such as making the transition from junior-to-senior level. Research suggests that accurate (affective) forecasting can play a key role in athletes` decision-making and post-retirement life quality. This presentation will focus on research with Olympic-level athletes from the UK, US and Canada. In this study participants were asked to make predictions on how they would feel about their retirement three months before and nine months after the Olympic Games they retired after. Results suggested athletes tended to under-estimate the amount of preparation required for their life after sport. Recommendations for interventions programmes will be discussed.